Pengaruh Kendaraan Berat Terhadap Polusi Suara dan Getaran di Pita Getar - Idham, Muhammad (Jurusan Teknik Sipil, 2017)
Increasing transportation mode becomes the increase of vehicles on the roads, it will impact to the pollution. The phenomena that appear in the last few years in the study areas is the rumble strips one solution for management transportation to give shock effect for road users that aware, however, it will be impacted to nosing and vibration on the roads. The research will be researcher noise level and vibration the heavy vehicles impact with case study Bengkalis island. The result indicated that the higher the heavy vehicles speed the smaller the vibration, while the noise level is getting bigger.